1912 N.J. Laws 366 - (:unkn) unknown (My University, 1912)
Ch. 225, 4: Every person selling a pistol, revolver or other firearm of a size which may be concealed upon the person whether such seller is a retail dealer, pawnbroker or otherwise, shall keep a register in which shall be entered at the time of sale the date of sale, name, age, occupation and residence of every purchaser of such a pistol, revolver or other firearm, together with the calibre, make, model, manufacturer's number or other mark of identification on such pistol, revolver or other firearm
Keywords: REGISTRATION